2014
DOI: 10.1021/ol501022d
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Regio- and Stereoselective Intermolecular Three-Component Oxyarylation of Allenes

Abstract: A copper(II)-catalyzed intermolecular three-component oxyarylation of allenes using arylboronic acids as a carbon source and TEMPO as an oxygen source is described. The reaction proceeded under mild conditions with high regio- and stereoselectivity and functional group tolerance. A plausible reaction mechanism is proposed, involving carbocupration of allenes, homolysis of the intervening allylcopper(II), and a radical TEMPO trap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…[4][5][6][7] However, few methods are currently available allowing for catalytic reactions of Cu-based carbon nucleophiles with allenes. 8 We developed and report herein our studies on Cu-catalyzed reactions of vinylidene cyclopropanes with carbon nucleophiles generated from 1,1-bisborylmethane and alkynyl boronates to deliver synthetically useful homopropargylic boronate and skipped diyne products.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] However, few methods are currently available allowing for catalytic reactions of Cu-based carbon nucleophiles with allenes. 8 We developed and report herein our studies on Cu-catalyzed reactions of vinylidene cyclopropanes with carbon nucleophiles generated from 1,1-bisborylmethane and alkynyl boronates to deliver synthetically useful homopropargylic boronate and skipped diyne products.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above observations, we propose a mechanism for the copper-mediated coupling of phenylboronic acid with diphenylmethanol, leading to triphenylmethane and boric acid ( Scheme 3 ). At the start of the cascade, the first step is the transmetallation of the copper(II) into phenylboronic acid to form reactive PhCu(OTf) ( 15 ) and B(OH) 2 (OTf) [ 61 ]. The intermediate 15 then reacts with diphenylmethanol 9 to provide the intermediate 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Shimizu and Kanai reported that allenes 73 undergo oxyarylation in the presence of a variety of aryl boronic acids 74 and TEMPO to yield β-arylated allylic alcohol derivatives 75 under copper catalysis ( Scheme 13 ). 35 Copper( i ) salts were also effective in the transformation but Cu(OTf) 2 was optimal. The mechanism is proposed to go through initial transmetallation of copper with aryl boronic acids to form aryl copper 76 ( Scheme 13B ).…”
Section: Future Prospects In Copper Catalysed Allene Functionalisatiomentioning
confidence: 99%